Introduction of Fundamental Movement Skill (FMS) in Elementary School - Desy Tya Maya Ningrum; Hafizah, Hafizah; Decenni Amelia; Yafi Velyan Mahyudi; Eldin Maulana; Rizqia, Rizqia (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2024)
Students' basic movements begins to develop in the elementary school phase, which must be developed to support the learning of physical education. This dedication discusses several approaches that teachers can use to teach basic movement skills to their students, as well as long-term benefits. Action research methods can be done in a community of sports teachers who will form collaboration with other teachers to find problems and find solutions. Thus, through such methods, participants can receive and implement learning management in support of the identification of sustainable student talents. The results of dedication are: 1) The range of activities carried out, 2) Continuous support, 3) Evaluation and Feedback, 4) Use of Help Tools, 5) Programme Action to Solve Problems. Identifying challenges in the accompaniment process, the leader and the dedication team will identify problems or obstacles encountered by participants in learning basic movement skills. Once the identification is obtained the problem will be formulated in the form of learning reflection for the next meeting. The community service activities, in the implementation of the activities, use playing learning methods and use the learning media that have been modified to have a positive effect on physical, cognitive, and social development. Games and media modified can motivate and attract the interest of children to be willing to train their activity and muscle development, reduce saturation, and improve the child's skills in a fun way.